2011
DOI: 10.1037/a0020722
|View full text |Cite
|
Sign up to set email alerts
|

Imitation and repetition of prosodic contour in vocal interaction at 3 months.

Abstract: This study investigates vocal imitation of prosodic contour in ongoing spontaneous interaction with 10- to 13-week-old infants. Audio recordings from naturalistic interactions between 20 mothers and infants were analyzed using a vocalization coding system that extracted the pitch and duration of individual vocalizations. Using these data, the authors categorized a sample of 1,359 vocalizations on the basis of 7 predetermined contours. Pairs of identical successive vocalizations were considered to be imitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 84 publications
0
49
0
Order By: Relevance
“…Therefore, the oscillators must be entrained in antiphase, giving the participants both a common rhythm, constituted by speech rate and length of comfortable pauses, and complementarity-readiness to take the floor must be opposite at any given moment for speaker and hearer. This ability seems to appear at a very early developmental stage (Gratier & Devouche, 2011;Murray & Trevarthen, 1985;Nadel, Carchon, Kervella, Marcelli, & Réserbat-Plantey, 1999;Spurrett & Cowley, 2004;Warlaumont, 2012).…”
Section: Complementaritymentioning
confidence: 99%
“…Therefore, the oscillators must be entrained in antiphase, giving the participants both a common rhythm, constituted by speech rate and length of comfortable pauses, and complementarity-readiness to take the floor must be opposite at any given moment for speaker and hearer. This ability seems to appear at a very early developmental stage (Gratier & Devouche, 2011;Murray & Trevarthen, 1985;Nadel, Carchon, Kervella, Marcelli, & Réserbat-Plantey, 1999;Spurrett & Cowley, 2004;Warlaumont, 2012).…”
Section: Complementaritymentioning
confidence: 99%
“…These pitch accents can be easily detected on sight by means of frequency analyzing programs that draw visible F0 pitch contours Van Puyvelde et al, 2010) and are even recognized by ear (Doolittle et al, 2014;Van Puyvelde et al, 2010). Therefore, the base of the vocal pitch analyses is similar to the identification of prosodic contours as applied, for instance, in a study of Gratier and Devouche (2011). Fig.…”
Section: A 3-step Methods Based On the Theory Of English Tonology Or Amentioning
confidence: 98%
“…This growing interest in the musical characteristics of mothers' speech has resulted in a series of acoustic studies that not only focused on ID speech but also examined the vocal co-construction between mothers and infants, highlighting the importance of specific micro-aspects such as pitch (Malloch, 1999(Malloch, /2000Van Puyvelde et al, 2010), timbre (Malloch, 1999(Malloch, /2000, prosodic contours (Gratier & Devouche, 2011), rhythm (Schögler, 1998) and timing (Gratier, 2003;Malloch, 1999Malloch, /2000 in the formation of a shared lived experience. These attempts to pinpoint spontaneous protomusical processes in the interpersonal connection between mothers and infants have revealed new concepts, such as spontaneous musicality (Malloch & Trevarthen, 2008), tonal synchrony (Van Puyvelde et al, 2010 and shared feelings of belonging (Gratier, 2008).…”
mentioning
confidence: 99%
“…While some empirical studies have reported mimicry of sounds as early as 2-6 months of age (e.g. Kuhl & Meltzoff, 1996;Kokkinaki & Kugiumutzakis, 2000;Gratier & Devouche, 2011), a phenomenon that could be facilitated by audio-visual congruence in the model (Legerstee, 1990), other data suggest that the ability to imitate does not fully develop until the second year of life (Jones, 2009). Imitation involves a variety of perceptuo-motor, cognitive and social skills which makes it one of the "building blocks from which spoken language develops in typical development" (Charman, 2006:106).…”
Section: Role Of Imitation In Speech and Languagementioning
confidence: 99%